Evidence of the color pattern variation in populations of Gymnotus pantanal (Gymnotiformes) from three streams in the upper Paraná River basin, Brazil - Vitor André Frana; Weferson Júnio da Graça; Éder André Gubiani; Jocicléia Thums Konerat; Vladimir Pavan Margarido (Neotropical Ichthyology, 2011)
Color pattern is an important character in the systematics and alpha-taxonomy of electric fishes of the genus Gymnotus. This paper presents evidence of color variation in populations of G. pantanal found in the streams Jacutinga and Pinheirinho, in the upper Paraná River basin, southern Brazil. Color variations were corroborated for morphological and cytogenetic data. Our results show the importance of integrating morphologic and cytogenetic data in the taxonomy of the Gymnotus species. O padrão de colorido é um caráter muito importante na sistemática e alfa taxonomia de espécies do gênero Gymnotus. O objetivo deste trabalho foi apresentar evidências de variação no padrão de colorido em populações locais de Gymnotus pantanal encontrados nos córregos Jacutinga e Pinheirinho, bacia do alto rio Paraná, sul do Brasil. A variação no padrão de colorido foi corroborada por dados morfológicos e citogenéticos. Nossos resultados demonstram a importância da integração de dados morfológicos e citogenéticos na taxonomia de espécies de Gymnotus.